A comunicação dos processos artísticos nos ambientes virtuais: análises e perspectivas - Moraes, Vânia de (2014)
Considering all educational practice also consists of a communicative practice , this proposal is resulted from an investigation by the architecture of virtual learning environments (VLE ) about three IES that offer superior Degree in Visual Arts , in a distance mode .. About the materials and methods, the investigation was done through exploratory research and utilization of educational materials available in AVA. The theoretical framework consists of publications related about studies of the Semiotics of Culture, the General Theory of Systems and Information Technology and Communication ( ICT ) , with emphasis on Instructional Design . Highlight for Lotman (1999 ) Beatalanffy (1977 ) . The research was also significant with the theoretical support of the Semiotics of Culture with Machado and Pinheiro , the General System Theory , with Vieira and Bunge , and with Vygotsky . The result did not favor interactive practice the act of teaching teach art , due to technical and pedagogical shifts . In this context , through instructional design , are desired continuous architectural proposals for balanced service user organizations representing the plural context and Brazilian mongrel